Child Quality and Child Quantity: Evidence from Bolivian Household Surveys - Sebastian Bredl (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Models built on the classical quality-quantity trade-off predict an increase in child quality and a decrease in child quantity in poor developing countries when parental wealth and educational levels increase. This paper tests this prediction empirically in a cross-sectional framework with data from Bolivian household surveys. Instead of focusing on actual fertility levels, the reported desired number of children is considered. The potential problem of ex-post rationalizing births – i.e. the adaptation of desired to actual fertility levels – is taken into account. The empirical findings are in line with the predictions of these models. Furthermore a weak but significant negative impact of fertility exceeding the desired level on educational outcomes is found.
Keywords: C21; D10; J24; 330